VIABILITAS BAKTERI ASAM LAKTAT (BAL) PADA PERMEN PROBIOTIK SIRSAK GUNUNG (Annona montana Macf) - Ambar Fidyasari; Fitri Eka Lestari; Anggraeni In Oktavia (Jurnal Inovasi Penelitian, 2022)
Mountain soursop (Annona montana Macf.) has secondary metabolites i.e. terpenoids and flavonoids which are powerful antioxidants. It is rarely used due to its unpleasant taste. Hence, to increase its economic value, this fruit has been new innovations into probiotic candy. Lactobacillus is a probiotic product commonly used, so this study used Lactobacillus casei. To meet the probiotic products requirement, the lactic acid bacteria must survive in the gastrointestinal tract and have a good stability and viability during the storage. This study has a purpose to determine the amount of storage stability on the viability of lactic acid bacteria in Mountain soursop (Annona montana Macf.) probiotic candy. The research used a descriptive analysis method, where the research results are described according to the data obtained from the total plate number of lactic acid bacteria. Based on the research that has been done, it can be concluded that the total lactic acid bacteria in the mountain soursop probiotic candy (Annona montana) on day 3 was 5.7 × 103 cfu/mL on day 5 of 4.8 × 103 cfu/mL, and on day 7 as much as 2.6 × 103 cfu/mL.